Virus to control cassava pest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Pesticide application to control insect attacks has often been shown to kill off the natural predators or parasites of the pest, whilst having little impact on the pest itself. This has proved to be the case with horn worm, a serious pest of...